Tapered CSRR-Based Sensor for Relative Permittivity Measurement With Application to Biomedical Microfluidic Sensing - Salem A. Alotaibi; Yepu Cui; Manos M. Tentzeris (IEEE Access)
This paper proposes miniaturized, lightweight and ultrasensitive planar metamaterial sensor for relative permittivity measurement of nondispersive materials. The proposed sensor is designed using a thin-substrate microstrip line loaded with tapered sectorial Complementary Split Ring Resonator (CSRR). Compared to similar state-of-the-art sensors, the proposed one is at least (25)% more sensitive with a wide dynamic range of the sensing related frequency. Moreover, unlike previously proposed sensors, the relative permittivity of a dielectric sample can be estimated using the variation of the minimum transmission frequency as well as the variation of the 10-dB sensor’s bandwidth which increases the integrity and accuracy of the obtained results. The minimum transmission frequency of the proposed sensor shifts by almost 7.6 GHz with a percentage change of 61% when the relative permittivity of the material under test (MUT) changes from 1 to 10. In addition, the 10-dB bandwidth is reduced by almost 7.7 GHz for the same MUT relative permittivity changes. Experimental measurements are in good agreement with the numerical findings. The paper includes a comprehensive sensitivity analysis that investigates the effect of resonator’s split length as well as its path width on the sensitivity and dynamic range of CSRR based sensors. Finally, the proposed sensor was used for microfluidic sensing to further demonstrate its practicality using different samples with different electrical properties. The sensor was able to provide distinct features for three different eye drops. The proposed sensor can be utilized as an effective permittivity sensor for various sensing applications such as displacement, nondestructive and biomedical sensing.